Representation of Motor Movements of Elementary School Students in the Lower Grades of Nusantara University Laboratory PGRI Kediri - Himawanto, Wasis; Kholis, Moh. Nur; Zawawi, M. Anis (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2024)
This research investigates the motor movement abilities of elementary school students at the Nusantara University PGRI Kediri Laboratory Elementary School using t-score conversion and norm categorization into five categories. Of the 146 students studied, the results showed that the distribution of motor skills included 33% of students in the "Poor" category, 44% in the "Medium" category, 11% in the "Good" category, and 13% in the "Very Good" category, with no students which falls into the "Very Poor" category. Analysis using t-score shows an average value of 152.4478 with significant variation (SD = 17.9229). This study confirms the importance of comprehensive evaluation and accurate statistical methods in understanding and improving students' motor skills in elementary education.